Transient expression of the cholecystokinin gene in male germ cells and accumulation of the peptide in the acrosomal granule: possible role of cholecystokinin in fertilization. - Persson, H (1989)
Expression of the gene encoding the neurotransmitter/neuromodulator cholecystokinin (CCK) was demonstrated in testis of several different species. Two testicular CCK mRNA transcripts of different sizes were detected, and studies on the ontogeny of CCK gene expression indicated that the gene was expressed in male germ cells. In situ hybridization revealed CCK mRNA-expressing cells in the peripheral parts of the seminiferous tubules. Biochemical identification showed that the majority of prepro-CCK products in the testis represented pro-CCK. Immunofluorescence studies revealed CCK-like peptides primarily in spermatocytes and spermatids of mouse, rat, and monkey. Immuno electron microscopy of monkey testis demonstrated CCK immunoreactivity in the acrosomal granule of spermatids. Hence, an interesting possibility is that CCK peptides can be released during the acrosome reaction and thus may be of importance in the fertilization process.